BRAIN, MIND AND MACHINE: WHAT ARE THE IMPLICATIONS OF DEEP BRAIN STIMULATION FOR PERCEPTIONS OF PERSONAL IDENTITY, AGENCY AND FREE WILL? - Lipsman, Nir (Bioethics, 2013)
Brain implants, such as Deep Brain Stimulation (DBS), which are designed to improve motor, mood and behavioural pathology, present unique challenges to our understanding of identity, agency and free will. This is because these devices can have visible effects on persons' physical and psychological properties yet are essentially undetectable when operating correctly. They can supplement and compensate for one's inherent abilities and faculties when they are compromised by neuropsychiatric disorders. Further, unlike talk therapy or pharmacological treatments, patients need not ‘do’ anything for the treatment to take effect. If one accepts, as we argue here, that brain implants are unique among implantable types of devices, then this can have significant implications for what it means to persist as the same person and be the source of one's thoughts and actions. By examining two of the most common indications for DBS in current use, namely in the motor (Parkinson's Disease) and psychiatric (Major Depression) domains, we further argue that although DBS, as it is currently applied, does not necessarily represent a unique threat to personal identity and agency per se, it introduces an unprecedented ‘third party’ into the debate on these concepts. In this way, DBS can be used as a tool to begin probing, both conceptually and empirically, some of philosophy's most perennial metaphysical questions.